Hospital-Acquired Hyponatremia in Children Following Hypotonic versus Isotonic Intravenous Fluids Infusion - Spyridon A. Karageorgos; Panagiotis Kratimenos; Ashley Landicho; Joshua Haratz; Louis Argentine; Amit Jain; Andrew D. McInnes; Margaret Fisher; Ioannis Koutroulis (MDPI AG, 2018)
Hypotonic solutions have been used in pediatrics for maintenance of intravenous (IV) hydration. However, recent randomized control trials and cohort studies have raised significant concerns for association with hospital-acquired hyponatremia (HAH). The study aimed to assess whether the use of hypotonic parenteral solutions (PS) compared with isotonic PS is associated with increased HAH risk in children with common pediatric conditions. Retrospective chart review of 472 patients aged 2 months to 18 years who received either isotonic or hypotonic PS as maintenance fluids. Administration of hypotonic PS was associated with a four-fold increase in risk of developing HAH in the univariate analysis, (unadjusted odds ratio (OR) = 3.99; 95% confidence interval (CI): 1.36–11.69, p = 0.01). Hypotonic PS were associated with HAH (p = 0.04) when adjusted for the level of admission serum CO2. There was a mean decrease of serum sodium of 0.53 mEq/L in the hypotonic group compared to the mean increase of 4.88 mEq/L in the isotonic group. These data suggest that hypotonic PS are associated with HAH in children admitted for common pediatric conditions. Isotonic PS should be considered as a safer choice for maintenance fluid hydration.